1987
DOI: 10.1021/bi00392a034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chromatin acceptor sites for the avian oviduct progesterone receptor using monoclonal antibodies

Abstract: Monoclonal antibodies (MAb) against the chromatin acceptor sites for the avian oviduct progesterone receptor were prepared with highly purified hen oviduct acceptor proteins reconstituted to hen DNA. Addition of the MAbs to a cell-free assay blocked progesterone receptor from chick oviduct (PRov) binding to native-like acceptor sites on nucleoacidic protein (NAP) representing a partially deproteinized chromatin, which has been shown to be enriched in these binding sites. However, the antibodies do not block PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…An acceptor-like protein has also been identified for binding the thyroid hormone receptors to the genomic DNA [Murray and Towle, 19891. A recent study using immunohistochemical techniques has shown that the RBF-1 is not only localized to the nucleus but present only in those cells known to contain PR (epithelial) [Zhuang et al, 19931. The immunohistochemical localization of RBF-1 confirms the results obtained with cruder localization approaches showing this protein to be primarily localized to the nuclei of cells [Schuchard et al, 1991a;Goldberger et al, 1987;Spelsberg et al, 1984;Hora et al, 19861. Localization of both RBF-1 and PR t o the nuclear interior is consistent with the observations that both steroid receptors and the nuclear acceptor proteins have been localized in the nuclear matrix [Barrack, 1987;Schuchard, 1991a1.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An acceptor-like protein has also been identified for binding the thyroid hormone receptors to the genomic DNA [Murray and Towle, 19891. A recent study using immunohistochemical techniques has shown that the RBF-1 is not only localized to the nucleus but present only in those cells known to contain PR (epithelial) [Zhuang et al, 19931. The immunohistochemical localization of RBF-1 confirms the results obtained with cruder localization approaches showing this protein to be primarily localized to the nuclei of cells [Schuchard et al, 1991a;Goldberger et al, 1987;Spelsberg et al, 1984;Hora et al, 19861. Localization of both RBF-1 and PR t o the nuclear interior is consistent with the observations that both steroid receptors and the nuclear acceptor proteins have been localized in the nuclear matrix [Barrack, 1987;Schuchard, 1991a1.…”
Section: Discussionsupporting
confidence: 80%
“…Selective removal of the chromatin protein fraction which contains RBF-1 results in the loss of the highest affinity class of PR binding sites. When RBF-1 is reconstituted back onto the avian genomic DNA, the specific binding of PR is regenerated [Spelsberg et al, 1984Hora et al, 1986;Goldberger et al, 1987;Schuchard et al, 1991bI. This protein has been purified to apparent homogeneity and shown to be hydrophobic with a M, = l o kDa as determined by SDS-PAGE [Schuchard et al, 1991a,b;Rejman et al, 19911.…”
mentioning
confidence: 99%
“…The RBF-1 protein has been purified to apparent homogeneity and partially characterized [Schuchard et al, 1991a,b;Rejman et al, 19911. Several hormone acceptor sites for several steroid-receptor systems have been partially characterized, and in some instances, the "acceptor" proteins identified [Spelsberg et al, 1983[Spelsberg et al, , 1984Schuchard et al, 1991a,b;Goldberger et al, 1987;Ruh et al, 1986Ruh et al, , 1987Klyzsejko-Stefanowicz et al, 1976;Lian and Spelsberg, 1982;Ross and Ruh, 1984;Foekens et al, 1985;Hora et al, 1986;Goldberger and Spelsberg, 1988;Murray and Towle, 1989;Rejman et al, 19911. All of these systems, in particular the one associated with the avian PR, have been studied exclusively in cell-free systems.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin acceptor sites for the avian oviduct progesterone receptor (PR) have been studied extensively and found to consist of complexes of specific acceptor proteins tightly bound t o specific DNA sequences [Spelsberg et al, 1972[Spelsberg et al, , 1984[Spelsberg et al, , 1987a[Spelsberg et al, ,b, 1988Schuchard et al, 1991a,b;Pikler et al, 1976;Kon and Spelsberg, 1982;Hora et al, 1986;Goldberger et al, 1987;Goldberger and Spelsberg, 1988;Rejman et al, 19911. The specificity of this interaction is highlighted by in vivo and in vitro studies which demonstrate that the binding of PR to avian oviduct chromatin is not only saturable and high affinity [Spelsberg et al, 1983[Spelsberg et al, , 1984[Spelsberg et al, , 1987aPikler et al, 19761, but also receptor dependent [Pikler et al, 19761 and receptor specific [Spelsberg et al, 1987a,b;Kon and Spelsberg, 19821.…”
mentioning
confidence: 99%
See 1 more Smart Citation